PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG PEMERIKSAAN TRIPLE ELIMINASI MELALUI EDUKASI - Iis Sopiah Suryani; Lina Marlina; Ai Rahmawati (Akademi Kebidanan Harapan Bunda Bima, 2026)
This community service program aimed to improve pregnant women’s knowledge regarding triple elimination examinations (HIV, Syphilis, Hepatitis B) through structured health education in Cipedes Village, West Java. The method used was participatory education with lectures, discussions, and distribution of educational leaflets. A total of 40 pregnant women attended the session. Pre- and post-test results showed a significant increase in knowledge scores (average pre-test 56.5 vs post-test 82.3). The findings indicate that health education interventions conducted by midwives are effective in raising awareness and compliance with maternal screening programs. This activity contributes to maternal and neonatal health improvement and supports national targets for triple elimination.